Research on the fuel loading patterns of the initial core in Chinese pebble-bed reactor HTR-PM. (August 2018) - Zhang, Jingyu; Guo, Jiong; Li, Fu; Sun, Yuliang
Highlights: The physical consideration on the fuel loading patterns of the initial core of HTR-PM is given. The initial core is proposed to be made up of low-enrichment fuel spheres and graphite spheres. Several representative schemes are simulated and analyzed using VSOP code. The volume fraction of fuel spheres in the initial core is proposed to range from 5/15 to 11/15. Abstract: Modular high-temperature gas-cooled reactor (HTGR) is a kind of safe and advanced nuclear energy system, which can provide electric power and high-temperature process-heat efficiently. At present, a 200 MWe demonstration plant, named high-temperature gas-cooled reactor – pebble-bed module (HTR-PM), is being built in China and is planned to be critical in one or two years. In this paper, the physical consideration on the fuel loading patterns of the initial core of HTR-PM is given, and the initial core of HTR-PM is proposed to be made up of low-enrichment fuel spheres and graphite spheres. Then several representative schemes are simulated using VSOP code. The relationship between the key physical parameters (fuel enrichment, flux distribution, temperature coefficient, power per fuel sphere, charging rate) and the volume fraction of fuel spheres in the initial core is analyzed. As a result, the feasible region of the volume fraction of fuel spheres in the initial core is determined as [5/15, 11/15]. The work of this paper can provide support for the fuel management of HTR-PM in the future.